2008
DOI: 10.1128/jcm.02438-07
|View full text |Cite
|
Sign up to set email alerts
|

Acute Infantile Gastroenteritis Associated with Human Enteric Viruses in Tunisia

Abstract: , investigated the incidence and the clinical role of various enteric viruses responsible for infantile gastroenteritis in 632 Tunisian children presenting in dispensaries (380 children) or hospitalized (252 children) for acute diarrhea. At least one enteric virus was found in each of 276 samples (43.7%). A single pathogen was observed in 234 samples, and mixed infections were found in 42 samples. In terms of frequency, rotavirus and norovirus were detected in 22.5 and 17.4% of the samples, respectively, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
142
6
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 45 publications
21
142
6
2
Order By: Relevance
“…Genotype G1 was observed to be broadly circulating in Korea, with overall incidences of 54.3%. This result is in agreement with the earlier findings that G1 was the most prevalent strain (45-81%) regardless of geographical area or season in Korea (16). Human G9 RoVs have recently been highlighted as the fifth most common strain in circulation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Genotype G1 was observed to be broadly circulating in Korea, with overall incidences of 54.3%. This result is in agreement with the earlier findings that G1 was the most prevalent strain (45-81%) regardless of geographical area or season in Korea (16). Human G9 RoVs have recently been highlighted as the fifth most common strain in circulation.…”
Section: Discussionsupporting
confidence: 83%
“…RoVs have shown a seasonal pattern of infection in developed countries, epidemic peaks occurring in the cooler c 2011 The Societies and Blackwell Publishing Asia Pty Ltd months of each year (16). In this study, RoVs were identified throughout the 12 month study period in Seoul, Korea.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NoV, RV, AsV and AdV were present in 26.5%, 19%, 11.7% and 4.7% respectively of cases as a single or co-pathogen with seasonal distribution from May to October. A similar finding was reported by SidiriLoulizi et al [22] from Tunisia, where RV was slightly more dominant than NoV (22.5 v 17.4%), followed by AsV (4.7%) and AdV (2.7%) in children hospitalized because of acute diarrhea. Distribution of viral gastroenteritis showed both a winter peak and a summer/autumn peak (May to October) in Tunis.…”
Section: Discussionsupporting
confidence: 74%
“…Enzyme immunosorbent assays have been used to study diarrheal infection for years and commercial kits with high sensitivity and specificity are readily available [20,21]. Despite this, only a few studies report the burden of enteric viruses in North Africa [13,22]. This report, the first comprehensive surveillance describing etiologies of enteric viruses and parasites from children with diarrhea seeking medical care, demonstrated that inclusion of additional laboratory tests significantly The previous publication by our colleagues [7] characterized the frequency of bacterial etiologies of diarrhea in the same region, but in our study, additional analyses illustrated the significance of enteric viral infection in the first year of life in Egyptian children, both as a sole pathogen and as part of what may be a true polymicrobial infection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47]. In contrast, other studies found no significant differences between the severity of rotavirus and norovirus infections [48][49][50][51]. One such study was conducted by us in Tunisia, and we attributed the severity of the norovirus infection to a lack of medical care at home and the delay to hospitalization for children infected with norovirus.…”
Section: Discussionmentioning
confidence: 99%